Pengaruh Intellectual Capital Terhadap Market Value dan Kinerja Keuangan - Angela Desiyanti Pangestu; Riesanti Edie Wijaya (Journal of Accounting and Investment, 2014)
The resource-based theory provides an epiphany about the existence of resources that potentially generate value added for a company competitive advantage. The theory emphasizes the existence of intellectual capital as levers of company success. However, the various studies produce inconsistent results one another. These studies take an Indonesia stock exchange setting with the market value and the financial performance as a measure of the success of the company. The result of this research shows that the disparity between human capital and structural capital in creating value added for the company.